Elite Company: Sourcing Trends in 2014–2017 Prestige Press Climate Change Editorials. Issue 4 (19th May 2021) - Garcia, Christopher J.; Proffitt, Jennifer M.
ABSTRACT: This manuscript examines the sourcing practices of climate change editorials published in The New York Times, Wall Street Journal, and USA Today between 2014 and 2017. Utilizing a critical political economic approach, we found that despite the ideological differences between the newspapers, each relied on sourcing practices that emphasized the views of elite political and economic actors with often no scientific training. Furthermore, our examination indicates a shared interest in politicizing scientific debates through weaponized sourcing practices that undermine science in favor of partisanship.